Female receptivity in Anastrepha ludens (Diptera: Tephritidae) is not modulated by male accessory gland products - Abraham, Solana (2014)
In numerous insects, accessory gland products (AGPs) transferred from males to females during mating are responsible for female sexual inhibition, but these products can be affected by male condition. Here, we investigated the effect of AGPs on female receptivity of the Mexican fruit fly Anastrepha ludens (Loew), and the effect of male and female strain, male irradiation, AGP dose and sexual activity period on the effectiveness of these AGPs in inhibiting female remating. Injections of aqueous extracts of male accessory glands into the abdomen of females did not reduce their receptivity either at 0.2 or 0.8 male equivalent. Females injected with AGPs behaved like virgin females and not as mated females. Neither male origin, female origin (wild versus mass-reared), nor male irradiation (sterile versus fertile males) had an effect in inhibiting female remating. Also, injections of glands obtained during the sexual calling period of males, or obtained during the morning when males are not sexually active had no effect on female remating behavior. Mated mass-reared females were more likely to remate than wild females. We conclude that inhibition of female sexual receptivity of A. ludens is mediated by factors other than AGPs, such as the number of sperm stored by females, the stimulus of copulation per se or more probably, mediated by a combination of factors. More research is needed to elucidate the role of AGPs in this species.